2017
DOI: 10.1016/j.neuropsychologia.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity associated with repetitive simulation of episodic counterfactual thoughts

Abstract: When people revisit past autobiographical events they often imagine alternative ways in which such events could have occurred. Often these episodic counterfactual thoughts (eCFT) are momentary and fleeting, but sometimes they are simulated frequently and repeatedly. However, little is known about the neural differences between frequently versus infrequently repeated eCFT. The current study explores this issue. In a three-session study, participants were asked to simulate alternative ways positive, negative, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Although less frequently emphasized, a few previous studies suggested a role for AI in self-reflection (Herwig et al 2012; Modinos et al 2009), as well as in the integration of self-related information during decisions about mental effort investment (Otto et al 2014), and in autobiographical self-relevant memories (Araujo et al 2015). In a recent study investigating episodic counterfactual thoughts, a process similar to rumination where people imagine alternative ways in which past events could have happened, De Brigard et al (2017) found increased insula activity, together with ACC, medial PFC, and inferior parietal cortex (De Brigard et al 2017), consistent with our results. Insula has also been associated with heightened interoception in mood disorders (Paulus and Stein 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Although less frequently emphasized, a few previous studies suggested a role for AI in self-reflection (Herwig et al 2012; Modinos et al 2009), as well as in the integration of self-related information during decisions about mental effort investment (Otto et al 2014), and in autobiographical self-relevant memories (Araujo et al 2015). In a recent study investigating episodic counterfactual thoughts, a process similar to rumination where people imagine alternative ways in which past events could have happened, De Brigard et al (2017) found increased insula activity, together with ACC, medial PFC, and inferior parietal cortex (De Brigard et al 2017), consistent with our results. Insula has also been associated with heightened interoception in mood disorders (Paulus and Stein 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The dorsal attention network is dedicated to the top-down control of attention 141 and encompasses the frontal eye field area, which likely involves both BAs 8 and 6 142 . Also BAs 20, 21 and 38 in the temporal lobe, which also show low Patel’s κ mean values, have been associated with memory 143146 and, especially, with language 147155 . BAs 21 and 38 are considered part of the DMN 156,157 , and have been found to be activated by empathy and perspective-taking tasks 158,159 .…”
Section: Discussionmentioning
confidence: 96%
“…Other research contrasting episodic counterfactual thinking and episodic future thinking has shown that contrary to increasing episodic future thoughts, increasing the availability of episodic counterfactual thoughts via repeated simulation reduces rather than increases their perceived plausibility (De Brigard, Szpunar, & Schacter, 2013). Neuroimaging evidence also shows differences in brain activity as a function of perceived plausibility because there is increased recruitment of core regions of the default network for episodic counterfactual thoughts perceived as plausible versus implausible (De Brigard, Addis, Ford, Schacter, & Giovanello, 2013; De Brigard, Parikh, Stewart, Szpunar, & Schacter, 2017). These and related results suggest, therefore, that how plausible we think a counterfactual event is may depend on the extent to which we see it as immoral, abnormal, salient, or easy to imagine or whether it has been repeatedly simulated.…”
Section: Modal Dimensionmentioning
confidence: 99%